Penyuluhan Hukum tentang Perlindungan Anak - Budi Handayani; Roidatus Shofiyah; Atmari Atmari; Tuti Herningtyas; Haniyah Haniyah (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Child protection is an important aspect in realizing the welfare and sustainability of the nation’s future generation. However, many people still do not fully understand children’s rights and the forms of legal protection available. This community service activity aims to improve public understanding and legal awareness regarding child protection through legal counseling programs. The method used was a participatory approach employing lectures, discussions, question-and-answer sessions, and simple case studies to help participants better understand the material presented. The target participants included parents, adolescents, and the general public within the village community. The counseling materials covered children’s rights, forms of violence against children, and legal protection mechanisms that can be pursued in cases of violations of children’s rights. The results of the activity showed an increase in public understanding of the importance of child protection and the role of families and communities in creating a safe and child-friendly environment. In addition, the community became more aware of legal measures that can be taken to prevent and address cases of violence against children. Therefore, this legal counseling activity proved effective in increasing public legal awareness regarding child protection and encouraging the creation of a more socially responsible environment that respects children’s rights.